Analysis of Verbal and Visual Signs in Positive Energy Challenge Video Advertisement - Maheswari, Cok Istri Agung Devi; Widiadnya, I Gusti Ayu Vina; Ariyaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2024)
This research aims to give further information about the visual and verbal signs contained in the video advertisement. Advertisement is the way to attract people's attention in promoting or selling the product and service. This study's main focus concerns the verbal sign and visual sign and their meanings that appeared in a video of Hyundai advertisement, which is Positive Energy Challenge. The descriptive qualitative method was applied in this study to convey the hidden meaning found in the verbal and visual signs in the video advertisement. The data were taken from the video of Positive Energy Challenge downloaded from YouTube. The study used the observation method in collecting the data through the note-taking technique. Regarding the analysis, there are two main theories used in this study. The first theory of semiotics by Ferdinand de Saussure (1983) is to find out the verbal sign and visual signs. The second is the theory of meaning by Barthes (1968) to analyze the meaning of the verbal sign and visual sign and supported by the theory of color terms proposed by Wierzbicka (1996). The result of the study shows that 5 verbal signs and 4 visual signs contained in the video advertisement have a positive meaning and can attract the attention of audiences.